2021
DOI: 10.1027/0227-5910/a000742
|View full text |Cite
|
Sign up to set email alerts
|

Association of Selected Area-Level Indicators With Suicide Mortality in Slovenian Municipalities

Abstract: Abstract. Background: With an average suicide rate of 20 per 100,000 in the last decade, Slovenia is above the EU average. There are considerable regional differences in suicide mortality within the country. Aim: We aimed to investigate the relationship between selected indicators at area level and the suicide rate in Slovenian municipalities. Method: Sociodemographic, socioeconomic, and (mental) health data in the years 2012–2016 were analyzed for 212 municipalities. Robust correlation and regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A single population based ecological study in Slovenia observed a univariate relationship between sickness absence duration per capita and the rate of suicide at a local area level, however this effect was not observed in statistical models that adjusted for area level socioeconomic and health service characteristics (50). Finally, a single cross-sectional study reported that taking sick leave was associated with decreased odds of current suicidal ideation in people receiving outpatient treatment for depression (51).…”
Section: Intentional Self-harmmentioning
confidence: 97%
“…A single population based ecological study in Slovenia observed a univariate relationship between sickness absence duration per capita and the rate of suicide at a local area level, however this effect was not observed in statistical models that adjusted for area level socioeconomic and health service characteristics (50). Finally, a single cross-sectional study reported that taking sick leave was associated with decreased odds of current suicidal ideation in people receiving outpatient treatment for depression (51).…”
Section: Intentional Self-harmmentioning
confidence: 97%
“…A single population based ecological study in Slovenia observed a univariate relationship between sickness absence duration per capita and the rate of suicide at a local area level, however this effect was not observed in statistical models that adjusted for area level socioeconomic and health service characteristics [51]. Finally, a single cross-sectional study reported that taking sick leave was associated with decreased odds of current suicidal ideation in people receiving outpatient treatment for depression [52].…”
Section: Plos Global Public Healthmentioning
confidence: 97%
“…Previous studies[ 13 - 16 ] indicated that suicide rates were the highest among males, elderly, single individuals, those with less schooling, family disintegration, unemployment, poverty, living in rural areas, with mental illness (especially alcohol misuse). Some authors indicated that males more frequently use highly lethal methods of suicide, such as hanging or firearms, in comparison to females[ 17 ].…”
Section: Introductionmentioning
confidence: 99%